Aplikasi Pengenalan Kosakata Bahasa Inggris "My Picture Dictionary" untuk Anak Sekolah Dasar Berbasis Android - Yesmaya, Violitta; Wongso, Rini; Swandyka, Imam; Zeavani, Muhammad Niko; Safrizal, Noverdi (Teknik dan Ilmu Komputer, 2014)
One of the technological advances in computer technology is the widespread phenomenon of mobile devices. Nowadays, many children often spend their time by playing games in mobile devices thereby reducing time to study. This makes children prefer playing than studyng. In fact, the development of mobile device technology can actually be used by parents to provide guidance in its use because mobile device is considered effective as a medium of education for children. Therefore, this research is develiped which is used to design the English vocabulary recognition application "My Picture Dictionary" by providing interactive information to general users of Android. Methodology in designing this application is by using the methods of analysis and design. The result of this design is the application running ÃÂ on a mobile device, with Android as the operating system. With this application, children are expected to be able to understand more about English while playing (interactive) in this application.ÃÂ Keywords: mobile devices, English, Android